Protocol for a cluster-randomised trial to determine the effects of advocacy actions on the salt content of processed foods - Trevena, Helen (BMC Public Health, 2016)
BACKGROUND: Corporate decisions affecting the composition of processed foods are a potent factor shaping the nutritional quality of the food supply. The addition of large quantities of salt to foods is incompatible with Australian Dietary Guidelines and the reformulation of processed foods to have less salt is a focus of non-governmental organisations (NGOs). There is evidence that advocacy can influence corporate behaviour but there are few data to define the effects of NGOs working in the food space. The aim of this study is to quantify the effects of advocacy delivered by a local NGO on the salt content of food products produced or marketed by companies in Australia. METHODS/DESIGN: This is a cluster-randomised controlled trial that will be done in Australia from 2013 to 2015 which includes 45 food companies. The 23 companies in the control group will receive no specific intervention whilst the 22 companies in the intervention group will receive an advocacy program based upon an established theory of change model. The primary outcome will be the mean change in sodium content (mg/100 g) of processed foods produced or marketed by intervention compared to control companies assessed at 24 months. Interim outcomes (statements of support, published nutrition policies, level of engagement, knowledge and use of technology to reduce salt, salt reduction plans, and support for national initiatives) will also be assessed and a qualitative evaluation will provide more detailed insight. DISCUSSION: This novel study will provide robust randomised evidence about the effects of advocacy on food company behaviour and the quality of the processed food supply. A finding of improved food company behaviour will highlight the potential for greater investment in advocacy whilst the opposite result will reinforce the importance of government-led initiatives for the improvement of the food supply. TRIAL REGISTRATION: ClinicalTrials.gov: NCT02373423. 26/02/2015 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-016-2743-4) contains supplementary material, which is available to authorized users.